ANALISIS POTENSI PARIWISATA SYARIAH DI NUSA TENGGARA BARAT (STUDI KASUS PANTAI LAWATA DI KOTA BIMA) - Wahyuni, Sri; Rahmawati, Rahmawati (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine the analysis of the potential for Islamic tourism in West Nusa Tenggara. This type of research is qualitative. The processed data is the result of interviews with managers and visitors on the lawata beach, West Nusa Tenggara. In the form of written or oral data on people (informants) and observed behavior. While the data research techniques used in this study were observation, interviews, and documentation. The number of respondents in this study were 6 people consisting of the tourism office and lawata beach visitors. The results of this study indicate that the tourism potential in West Nusa Tenggara has great potential, this is evidenced by the increase in visitors from 2018 to 2019 of 60.36%. However, the Tourism Office continues to make efforts to improve infrastructure improvements on the lawata beach, to attract visitors. either from within the Kota Bima area or from outside the region as a step towards increasing regional income in the City of Bima.Keywords: Potential of Sharia Touris